John Steinbeck at the excavation of Glastonbury Abbey - Unknown:::Creator:::::::::::: (England; Creech Hill, Somerset, 2022)
John Steinbeck standing at the fence at the excavation of Glastonbury Abbey, a monastery in Glastonbury, Somerset. John and Elaine were staying at nearby Discove Cottage while he was working on Acts of King Arthur. From at least the 12th century the Glastonbury area has been associated with the legend of King Arthur, a connection promoted by medieval monks who asserted that Glastonbury was Avalon. In 1191 the monks alleged the discovery of King Arthur and Queen Guinevere's tomb in the cemetery. Original in safe.